Faktor-Faktor Yang Memengaruhi Kepatuhan Pengobatan Pada Pasien TB - Ryansyah, Irgie Catur; Martilova, Sonia; Putri, Kartika; Sinaga, Evi Susanti (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
An infectious disease known as tuberculosis (TB) is one of the world's top causes of mortality and a significant contributor to health issues. Until recently, TB—rather than HIV/AIDS—was the most common infectious disease to cause death. Mycobacterium tuberculosis, the bacillus that causes tuberculosis, is released into the air when a person with the disease coughs or removes the bacteria. Without treatment, TB disease has a significant mortality rate (about 50%). Approximately 85% of patients can be treated with the current treatment guidelines (OAT medications for 4-6 months). This study examined the variables affecting TB patients' treatment adherence. A cross-sectional research design and the Fisher Exact test were utilized in this study. This study employed a consecutive, non-random sampling technique. Forty-four people made up the survey's sample size. Based on the analysis's findings, it was discovered that knowledge, side effects, the involvement of the family/PMO, distance, and perceptions of self-medication significantly influenced treatment adherence. There is no relationship between the function of TB officers and accessibility to transportation to treatment adherence.